(3CfhGQ GdYbhd ef CTYGQ hUj GdQShds - (3GdfjSGHhQj, GdcjOQj, CHh GdMSf, bWH GdOjf, eMeO Hf GdMSjf Hf GdMSf, J (B576 (3g`s ((3YHO GdUeO Hf eMeO GdGUagGfjs)
(3ChdgG (B:s
(3bGd CejQ GdeDefjf hEeGe GdeJbjf(B.... : (3GdfGS ef LgI GdJeKGd CcaGA (B*** (3CHhge BOe hGdCe MhGAs
(3BNQgG (B:s
...(3gPG eG CcOi Edjg cOj hCOi Edjg LgOj ef GdJbGW gPg GdOQQ GdaQjOI(B...(3hdG JPgdf Yf bhdj ajg TYQG(B: ... (3ajg GdeYGdj hajg GdaVd eLJeYG (B*** (3daVd UGMHg aj GdYGdejf Ydjs
(3GdhQbI GdChdi HgG BKGQ WeS eMJ HYV GdCHjGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B248s
(3GdPQjYI(B:(3L(B2(3,U(B241(3,b(B1697s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdCOHs